2015
DOI: 10.1186/s40409-015-0014-y
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial potential of a basic phospholipase A2 (VRV-PL-VIIIa) from Daboia russelii pulchella (Russell’s viper) venom

Abstract: BackgroundMicrobial/bacterial resistance against antibiotics poses a serious threat to public health. Furthermore, the side effects of these antibiotics have stimulated tremendous interest in developing new molecules from diverse organisms as therapeutic agents. This study evaluates the antibacterial potential of a basic protein, Vipera russellii venom phospholipase A2 fraction VIIIa (VRV-PL-VIIIa), from Daboia russelii pulchella venom against gram-positive and gram-negative bacteria.MethodsThe antibacterial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 33 publications
3
15
0
1
Order By: Relevance
“…The PLA 2 Lys 49 from Lachesis muta venom, also belonging to the Viperidae family, showed antimicrobial activity against S. aureus ATCC 29213 at 0.9 µM. Similarly, studies of a basic PLA 2 isolated from Daboia russelii (Viperidae), showed better antimicrobial effects for Gram-positive bacteria in comparison with that for Gram-negative bacteria [48,49]. These data corroborate our findings.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The PLA 2 Lys 49 from Lachesis muta venom, also belonging to the Viperidae family, showed antimicrobial activity against S. aureus ATCC 29213 at 0.9 µM. Similarly, studies of a basic PLA 2 isolated from Daboia russelii (Viperidae), showed better antimicrobial effects for Gram-positive bacteria in comparison with that for Gram-negative bacteria [48,49]. These data corroborate our findings.…”
Section: Discussionsupporting
confidence: 89%
“…This is a basic characteristic of this type of PLA 2 , determining a PLA 2 Lys 49 . Likewise, the enzymatic activity of a PLA 2 from Bothrops neuwiedi urutu, which contains Lys 49 , was absent when the synthetic substrate 4N 3 OBA was used [37,41]. Similarly, studies using the substrate 4N 3 OBA compared the catalytic activity of a PLA 2 (Bmaj-9) isolated from the venom of the snake Bothrops marajoensis with the crude venom of the same snake.…”
Section: Discussionmentioning
confidence: 99%
“…Studies related to molecules completely isolated from Viperidae venoms revealed different enzymatic classes with antibacterial properties, such as phospholipases A2, metalloproteases and LAAOs (DE LIMA et al, 2005;WEI et al, 2006;XU et al, 2007;OKUBO et al, 2012;SAMY et al, 2012;SUDHARSHAN;DHANANJAYA, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These molecules are also found in dromedary tears and showed activity against both gram positive and negative bacteria [ 60 ]. Thus, a PLA 2 isolated from Daboia Russelli venom was able to strongly inhibit gram negative bacteria and also showed activity against gram positive bacteria isolated from human [ 61 ] . Therefore, we also assume the protective action in toad skin.…”
Section: Discussionmentioning
confidence: 99%